2016
DOI: 10.1097/ta.0000000000001101
|View full text |Cite
|
Sign up to set email alerts
|

Managing the surge in demand for blood following mass casualty events

Abstract: Therapeutic/care management study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…34 We then created a model of casualty flow and blood utilisation by hospitals during a mass casualty event. 35 We populated this with the data collected from the literature, our specific investigations and the results of interviews with hospital staff and specialists. Once the model was constructed (Figure 16), we could modify parameters to investigate the benefits of alternative methods of utilising and preserving blood resources during such events.…”
mentioning
confidence: 99%
“…34 We then created a model of casualty flow and blood utilisation by hospitals during a mass casualty event. 35 We populated this with the data collected from the literature, our specific investigations and the results of interviews with hospital staff and specialists. Once the model was constructed (Figure 16), we could modify parameters to investigate the benefits of alternative methods of utilising and preserving blood resources during such events.…”
mentioning
confidence: 99%
“…They have also discussed emergency donor calling and alternatives for transfusion. Simon Glasgow et al have shown the importance of an automated system to redistribute the blood stocks for trauma centres [16]. In that publication, they have described a computerized simulation model in a trauma center in the United Kingdom that has shown the efficacy of prioritizing.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the administration of blood, unlike crystalloid, is limited by its availability, which is tested during MCEs as many patients require the use of massive transfusion protocol. Based on prior MCEs, the highest demand for blood is during the initial 4 hrs when the most gravely injured patients are brought to the hospital, using two-thirds of the total blood transfused 3638…”
Section: Discussionmentioning
confidence: 99%
“…A study using a computerized simulation model of a UK major trauma center found that even small volume MCEs could overwhelm trauma centers’ blood supplies and restocking would be necessary. The authors also suggest a central supplier for blood as a solution for the massive demand for blood during MCE 37,38…”
Section: Discussionmentioning
confidence: 99%